Secure Data Management: An Implementation of Advanced Encryption Standard in a Flutter-Based Notes App - Adetokunbo Abayomi Adenowo; Mary A. Adedoyin; Oluwasegun J. Adebiyi (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2026)
Given increasingly critical concerns about data security in the digital age, safeguard of sensitive information in mobile applications due to its global interconnectivity becomes an imperative. This research focuses on the protection of information on mobile applications, demonstrated through the design, development and evaluation of a Flutter-based Notes App that employs an encryption algorithm to ensure confidentiality and integrity of user data. Specifically, this research adopts the 256-bit Advanced Encryption Standard (AES) as the core mechanism of the Notes App, on assumption of its robust security features that it ensures data protection during both storage and transmission. To ascertain the choice, it compares the performance of the AES- 256 against that of 128-bit and 192-bit key sizes using key metrics such as encryption and decryption time, memory usage, power consumption, and error rate. Programmatically generated dataset, alongside graphical analyses, where used to illustrate the performance differences across the three key sizes. Findings from the aforementioned, reveal that while AES-256 incurs marginally higher resource usage compared to its smaller key-size counterparts, it delivers significantly enhanced security. The increase in processing time and memory usage shows a negligible impact on performance, affirming its practicality for real-world applications. The seamless operation of the Notes App during encryption and decryption processes further validated the suitability of AES-256 for mobile platforms. It is therefore safe to conclude that AES-256 provides the optimal balance between security and performance, thus makes it the preferred choice for protecting sensitive information in mobile applications.